IMPLEMENTASI KURIKULUM BELAJAR MANDIRI MATA PELAJARAN PJOK DI SEKOLAH DASAR KABUPATEN BERINGIN - Dani Alfa Sumitra (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The purpose of this study was to determine the application of the independent learning curriculum in PJOK learning in SD in Beringin District. This type of research is descriptive quantitative. The samples used in this study were all PJOK subject teachers who had attended seminars/training of the independent learning curriculum, totaling 5 samples and 2 students at each SD in Beringin sub-district, totaling 10 samples, so that the total sample in this study was 15. Hypothesis testing using SPSS 25. Based on the results of research on the application of the independent curriculum to learn PJOK subjects ini Beringin District, as many as 62.5% of teachers stated that it was running well and 37.5% of teachers stated that it was running moderately or quite well. Meanwhile, 62.5% of students stated that they had run well and 37.5% of students stated that they were running moderately or quite well.